2017
DOI: 10.5812/ijhrba.63237
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Consistent Condom Use Among Iranians Living with HIV/AIDS: Implication for Prevention

Abstract: Background: Individuals that are HIV positive can transmit the infection through unprotected sex. Objectives: The present study aimed to evaluate the prevalence and determinants of consistent condom use among Iranian people living with HIV/AIDS as one of the most stigmatized and hard-to-access groups in this country. Patients and Methods: This cross-sectional study was conducted in Tehran, Iran. A total of 400 heterosexuals living with HIV/AIDS were sampled from 5 behavioral consulting centers through a purpos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…HIV-positive people can spread the illness through unprotected sex ( 8 ), but the disease can be avoided if populations are educated about the risks ( 9 ). Abstain, Be Faithful, or Reduce the Number of Sexual Partners, and/or Use a Condom is an HIV/AIDS prevention strategy that is most narrowly defined as Abstain, Be Faithful, or Reduce the Number of Sexual Partners, and/or Use a Condom ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…HIV-positive people can spread the illness through unprotected sex ( 8 ), but the disease can be avoided if populations are educated about the risks ( 9 ). Abstain, Be Faithful, or Reduce the Number of Sexual Partners, and/or Use a Condom is an HIV/AIDS prevention strategy that is most narrowly defined as Abstain, Be Faithful, or Reduce the Number of Sexual Partners, and/or Use a Condom ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent condom use reduces the probability of HIV transmission per sex act by as much as 95% and reduces the annual HIV incidence in sero-discordant couples by 90-95% when used consistently [17]. However, risky sexual behaviour among HIV-positive people was reported in many studies, and consistent condom use varies from 16.7% [18] to 43% [19]. In another study from Iran, only 25% of people living with HIV always used condoms in the preceding year [20].…”
Section: Discussionmentioning
confidence: 99%
“…The participants had a moderate awareness about HIV prevention. Studies revealed that consistent condom use is associated with participation in an HIV prevention course, knowledge of unsafe sex consequences, and having an HIV-positive sexual partner [18]. However, many highrisk groups do not have adequate awareness of the modes of transmission of HIV, doubt about the role of condoms in preventing HIV, and face reluctance of sexual partners to use condoms due to reduced sexual pleasure [21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Iranian studies of condom use in PLWH and other at-risk groups with mood disorders are few. 14 , 15 , 16 Given the importance of condoms in preventing STIs, this study aimed to identify associations between depression, sleep quality and condom use in this cohort of PLWH.…”
Section: Introductionmentioning
confidence: 99%